Pengurangan Limbah dengan Penerapan Metode Just in Time di PT. Uwe Molino Luwuk - -, siswanto (Journal of Industrial System Engineering and Management, 2024)
The manufacturing industry is one of the important sectors in the Indonesian economy. PT. Uwe Molino Luwuk is one of the manufacturing companies that offers bottled drinking water (AMDK) products. This company still has several problems related to waste in its production process. This situation is also reflected in the loss of time during the production process. This waste can cause great losses for the company. This study aims to optimize production to reduce waste can be done by applying the Just In Time (JIT) method through the Value Stream Mapping (VSM) data analysis technique. The results of the study showed that the dominant waste in the top order was waiting. Developing improvements from the current to the future state, the lead time value of the material on the production floor was faster, in the VSM before 510 minutes while the lead time of the VSM after was 310 minutes. So there is a reduction in time of around 60.7%.